Kemampuan Pengguna dan Attitude Toward Change Memoderasi Pengaruh Perceived Usefulness pada Kinerja Sistem Informasi Akuntansi - Putra, I Kadek Dwi Handika; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi, 2021)
The goal of this study is to examine the impact of perceived usefulness on the performance of accounting information systems, with user ability and attitude toward change serving as moderating variables. The instrument used in this study was a questionnaire distributed to 106 employees of the Village Credit Institution (LPD) Sukawati District. In this study, moderated regression analysis was used as an analytical technique. The test results show that perceived usefulness has a positive effect on the performance of accounting information systems, that user ability has a positive effect on the performance of accounting information systems, and that perceived usefulness has a negative effect on the performance of accounting information systems. The attitude toward change has a positive effect on the performance of accounting information systems, and the ability variable users do not moderate the effect of perceived usefulness on the performance of accounting information systems. Keywords: Perceived Usefulness; Accounting Information System Performance; User Capabilities; Attitude Toward Change.